Pengaruh Media Video Berbasis Kearifan Lokal Gotong Royong Pertanian Dengan Konsep Kegiatan Ekonomi Terhadap Hasil Belajar IPAS Siswa Kelas Tinggi di SD Negeri Raulo - M, Baharia; Syarifuddin, Syarifuddin; Saripuddin, Saripuddin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to find out 1. To find out the influence of local wisdom-based video media on high class students at Raulo State Elementary School. 2) To find out the description of the implementation of economic activity concept material in science and science learning for high class students at Raulo State Elementary School. And 3) To analyze the influence of video media based on local wisdom of agricultural mutual cooperation with the concept of economic activity on high class students' science and science learning outcomes at Raulo State Elementary School.  This type of research is quantitative research.  The population of this study was all high class students, namely 43 students in grades 4, 5 and 6 at SD Negeri Raulo. The sampling technique used in this research is the saturated sampling technique so that the entire population becomes the research sample. Data collection techniques use research questionnaires, observation and documentation, while data analysis techniques use descriptive analysis and regression analysis. The research results show that the calculated t value is greater than the t table, so it can be concluded that there is a positive and significant influence of the use of Video Media Based on Local Wisdom of Agricultural Mutual Cooperation with the Concept of Economic Activities on the science and science learning outcomes of high class students at Raulo State Elementary School. Local culture-based learning media not only helps students understand concepts contextually, but also instills social and cultural values that are relevant to students' daily lives.